Chronic Invasive Aspergillosis caused by Aspergillus viridinutans - Donald C. Vinh; Yvonne R. Shea; Pamela A. Jones; Alexandra F. Freeman; Adrian Zelazny; Steven M. Holland (Emerging Infectious Diseases, 2009)
Aspergillus viridinutans, a mold phenotypically resembling A. fumigatus, was identified by gene sequence analyses from 2 patients. Disease was distinct from typical aspergillosis, being chronic and spreading in a contiguous manner across anatomical planes. We emphasize the recognition of fumigati-mimetic molds as agents of chronic or refractory aspergillosis.